Assessment of effectiveness of fetal medicine foundation calculator in predicting risk for preterm preeclampsia using first trimester mean uterine artery pulsatility index and maternal factors in Indian population - A, Anil; Varghese V., Binoj; John, Afra (International Journal of Research in Medical Sciences, 2022)
Background: Preeclampsia (PE) is a hypertensive disorder of pregnancy associated with significant maternal morbidity and mortality. The outcome of the disease depends to a large extent on risk factors, maternal vascular responsiveness, screening performance and prevention effectiveness. Fetal medicine foundation has developed an online calculator that predicts the risk for PE in pregnant woman in first trimester using MUAPI (mean uterine artery pulsatility index) and maternal factors. Methods: Diagnostic test evaluation of FMF (fetal medicine foundation) calculator done using data collected from consenting 316 women with singleton pregnancy between the gestational age 11 weeks to 14 weeks+1 day who fulfilled inclusion and exclusion criteria. All cases were followed up and results were analyzed statistically. Results: FMF calculator predicted a high-risk population of 12 pregnant women. On follow up of 316 subjects 13 pregnant women developed preterm preeclampsia with an incidence of 4.1%. Among high-risk population 9 subjects developed preterm PE and among the 304 cases in low-risk group 4 patient developed preterm PE. In this study sensitivity of FMF calculator was 69.2% and specificity was 99% with a PPV of 75, NPV of 98.6, positive likelihood ratio of 69.9 and diagnostic odds ratio of 225. The area under ROC was 0.841 with 95% CI (0.711-0.972) was high indicating that the algorithm was able to differentiate between pregnant women at high or low risk for preterm PE. Conclusions: This study concludes that the algorithm used in FMF calculator in first trimester is highly specific and have high sensitivity for predicting preterm PE and can be used in routine clinical practice to identify women at high risk.